Auxotrophic mutant of Staphylococcus aureus interferes with nasal colonization by the wild type - Barbagelata, María Sol (2011)
Staphylococcus aureus nasal carriage is a risk factor for infection in humans, particularly in the hospital setting. Bacterial interference was used as an alternative strategy for the prevention of upper respiratory, urogenital and gastrointestinal tract infections. This study was designed to assess if the administration of a live-attenuated aroA mutant of S. aureus is useful as a potential approach to prevent transient staphylococcal nasal carriage by virulent strains. We constructed an aroA mutant of S. aureus Newman strain by homologous recombination. The auxotrophic NK41 mutant was attenuated as determined by the increase of the LD50 after intraperitoneal challenge. In mice, previous nasal colonization with the NK41 mutant significantly reduced the number of CFU of S. aureus (HU-71 and Hde288) clinical isolates and the parental Newman strain. The NK41 mutant was unable to induce a pro-inflammatory response and to damage the invaded human respiratory epithelial cells. Moreover, the cells previously or simultaneously infected with the NK41 mutant were invaded by virulent strains in a significantly lower degree than those of the control group. In conclusion, the attenuated NK41 mutant interfered with the colonization and establishment of pathogenic strains of S. aureus, which produce severe infections. © 2011 Institut Pasteur.